Fiqh Kelautan; Tinjauan Teoritis dan Praktis Pelaksanaan Ibadah Sholat di atas Kapal - Imam Khoirul Ulumuddin (Universitas Wahid Hasyim Semarang, 2020)
The five daily prayers are worship that tomorrow in the hereafter will be held accountable for the first time, which is obligatory for every Muslim who is still alive and has perfect intellect wherever and under any circumstances, both at sea and on land, whether he is in vehicles or not, one of the modes of transportation is ships, and usually someone traveling or working using a ship takes a long time, between the pillars of prayer is facing the Qibla, which not many people know about it, so theoretical guidance is needed. and practical in carrying out prayers while someone is on a Ship. Abstrak Sholat Fardhu merupakan salah satu ibadah yang wajib dilaksanakan bagi setiap muslim yang sudah mukalaf baik di darat maupun di laut dan dalam keadaan apapun selama seorang muslim tersebut masih bernafas dan tidak hilang akalnya. Jika meninggalkannya tanpa ada alasan yang diperbolehkan agama, maka hukumnya dosa, karenanya merupakan ibadah yang pertama kali dipertanyakan di hadapan Allah SWT.